The Role of Financial Strategies for MSMEs in Responding to Macroeconomic Uncertainty: A Literature Review and Secondary Data Analysis - Putri Pratiwi; Silvia Fardila Soliha (LPPM Universitas Sains dan Teknologi Komputer, 2025)
Macroeconomic uncertainty poses a structural challenge for the sustainability of micro, small, and medium enterprises (MSMEs) in Indonesia. Fluctuations in inflation, benchmark interest rates, and exchange rates have a direct impact on liquidity, cost structures, and investment decisions. This study aims to explore the types of financial strategies adopted by MSMEs in response to macroeconomic pressures using a systematic literature review and secondary data analysis covering the period from 2019 to May 2024. Data were sourced from official national institutions, including the Central Bureau of Statistics, Bank Indonesia, the Ministry of Cooperatives and MSMEs, as well as relevant academic literature. The findings reveal that MSME financial strategies can be categorized into three key domains: cash management, cost control, and investment planning. MSMEs employing flexible strategies—such as increasing cash buffers, reducing operational costs, and diversifying products or financing sources—demonstrate higher resilience in the face of economic volatility. This study contributes theoretically by enriching the framework of financial adaptation for MSMEs and practically by informing financial literacy programs and policy design. The study also acknowledges limitations in the use of aggregate secondary data and recommends that future research adopt a mixed-method approach to capture undocumented informal financial practices at the grassroots level